Grammatical Interference On English Caption On Facebook Group’s “We Are ASEAN” - Mukshin Berry Chandra; Susilo Susilo; Desy Rusmawaty (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2021)
Abstract In this era, social media become a new way to connect the people. Platform such as, Facebook, Instagram, Twitter are examples of social media that use by large people. People not only share their photos or videos but they also can share their opinions and their knowledge to others as the way to build communication as social beings. On social media, there is a tool to make a group. Usually people make a group on social media based on their background, hobbies and discussion about certain issues. On Facebook group there is a group consisting of people from South East Asia named